The Participation in the Conservation of Local Wisdom on Producing Chaiya Salted Eggs in Chaiya District, Surat Thani Province - เพชรสถิตย์ พงษ์ศักดิ์ (Academic Journal of North Bangkok University, 2020)
This qualitative research on the Participation in the Conservation of Local Wisdom, producing Chaiya Salted Eggs in Chaiya district, Surat Thani province aimed to study 1) the transfer of local wisdom, Chaiya Salted Eggs making, and 2) the participation in preserving the local wisdom, Chaiya Salted Eggs production in Chaiya district, Surat Thani province. The results are as follows: Transferring of local wisdom, producing Chaiya Salted Eggs, has been found from generation to generation, relay within colleagues and broadcasting by organizing in a form of learning resources by means of lecture, demonstration, and real action focusing on raw material preparation and production processes. The goal of the relay is to develop, inherit and preserve the identity of Chaiya Salted Eggs. Participation in preserving the local wisdom, producing Chaiya Salted Eggs, found that the participation is divided into 3 parts, which are participation from the government, private sector, the public and local organization. The participation characteristics of each sector are different depending on the role and responsibilities of that sector, but still have the same goal of inheriting and preserving the identity of Chaiya Salted Eggs.